2022
DOI: 10.14309/ctg.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Gastrointestinal Transit Times in Colon Capsule Endoscopy

Abstract: INTRODUCTION: Optimizing the accuracy of colon capsule endoscopy (CCE) requires high completion rates.To prevent incomplete CCE, we aimed to identify predictors associated with slow CCE transit times. METHODS:In this population-based study, participants received CCE with a split-dose polyethylene glycol bowel preparation and booster regimen (0.5 L oral sulfate solution and 10 mg metoclopramide if capsule remained in stomach for > 1 hour). The following predictors were assessed: age, sex, body mass index (BMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…A comparable study to ours conducted by Moen et al has recently been published 21 . In their similarly sized study (n=451), they found a range of predictors associated with a complete test, including increased patient age, which contradicts our results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A comparable study to ours conducted by Moen et al has recently been published 21 . In their similarly sized study (n=451), they found a range of predictors associated with a complete test, including increased patient age, which contradicts our results.…”
Section: Discussionsupporting
confidence: 87%
“…A comparable study to ours, conducted by Moen et al., has recently been published [21]. In their similarly sized study ( n = 451), Moen et al.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study conducted in Nederland by Moen et al . 39 examined the factors affecting transit times in CCE. The study, which included 451 participants, is the largest to date to investigate possible predictors of CCE transit times.…”
Section: Influential Factors Affecting Cr In Ccementioning
confidence: 99%